Analisis Konsep Self-Regulated Learning dalam Mitigasi Bahaya Nomophobia pada Komunikasi Digital Gen Z - Ni Putu Hana Intan Pratiwi; Ni Putu Intan Permatasari (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
Rapid develpments in the field of communication and information technology have triggered new challenges among Generation Z (Gen Z). This study was motivated by the increasing use of smartphones, which has led to technological dependence and triggered the risk of nomophobia (no mobile phone phobia), as well as the need to find adaptive methods that are useful for Gen Z in managing their use of digital devices. The purpose of this study is to analyze how the concept of Self-Regulated Learning (SRL) as a mitigation approach can help Gen Z students manage digital communication on smartphones so that they can avoid the risk of nomophobia. This study uses a qualitative approach with descriptive methods through observation, interviews, and documentation studies, as well as data validity techniques through triangulation. This study involved eight Gen Z students in Denpasar who actively use smartphones, including for academic purpose, and two lecturers in the field of psychology. The results showed that the application of the SRL concept with three main phases: the forethought phase (planning), the performance phase (implementation), and the self-reflection phase (evaluation process), proved to be effective as mitigation strategy for nomophobia symptoms. Gen Z students who used SRL showed developments in self-control and the ability to manage digital distractions. In concluion, SRL proved to be a proactive internal mechanism that enables Gen Z to became disciplined and responsible users of digital technology.